IMPROVING STUDENTS’ ACHIEVEMENT IN UNDERSTANDING AND CREATING FANTASY STORIES THROUGH PROJECT BASED LEARNING IN CLASS VIIC OF MTSN 1 WEST ACEH - Hayati, Cut Intan; Husaini, Husaini; Wardiana, Wardiana (Program Studi Pendidikan Bahasa Indonesia FKIP-UNIVA Medan, 2021)
The purpose of this study was to improve students’ achievement in understanding and creating fantasy stories through project-based learning in Class VIIC of MTsN 1 West Aceh. The method used in this study was Action Research which consisted of 2 (two) cycles, and each cycle consisted of: Planning, Implementation, Observation, and Reflection. Based on the results of this action research, it was found that Project Based Learning can Improve students’ achievement in Understanding the Materials and Creating Fantasy Stories in Class VIIC of MTsN 1 West Aceh. Furthermore, the researcher recommends: (1) For teachers who have the same difficulties, they can apply Project Based Learning to improve the students’ achievement. (2) In order to get maximum results, it is hoped that teachers will make Project Based Learning more interesting and varied.